Red blood cell pathophysiology : comparative and diagnostic aspects - Weber, Brandon (Division of Chemical Pathology, 2023)
Captive black rhinoceroses in the United States are threatened by three major clinical disorders. Among these, haemolytic anaemia ranks as the number one cause of death. The object of this study therefore was to determine the metabolic lesion responsible for the haemolytic anaemia. Since black rhinoceros red blood cells were shown to be susceptible to oxidative stress, the first stage of the work focused on the characterisation of the hexose monophosphate shunt in these cells. Results were compared to human red blood cells. To determine how these cells responded to oxidative stress and to stimulation of this pathway, rhinoceros red blood cells were incubated with the known shunt stimulants ascorbate and methylene blue. Red blood cells were incubated with 14C-Iabelled glucose and then acid extracted. The rate of flux through the shunt was measured by counting 14C trapped on a filter placed inside the incubation vessel and saturated with NaOH. Red cell extracts were used for lactate and reduced glutathione determinations. These experiments showed that black rhinoceros red blood cells were capable of increasing flux through the shunt in response to oxidative stress although the magnitude of this response was significantly lower than that observed in human red blood cells. To determine whether the cells were capable of recycling metabolites through the shunt in response to prolonged oxidative stress, the red cells were incubated with 2-14C-Iabelled glucose. Recycling through the shunt was observed to function efficiently in these cells. Since no particular metabolic lesion could be defined with respect to the functioning of the lIMP, we shifted our attention to an unusual peak with cytidine-like absorbance properties which dominated the rhinoceros HPLC profile. A range of cytidine nucleotides and other nucleotides were analysed by reverse phase HPLC in an attempt to match the elution position of the unknown peak. This search yielded a surprising candidate, the amino acid tyrosine. Co-elution of this peak with standard tyrosine strengthened this identification. Diode array analysis of the HPLC peak yielded an identical wavelength maximum to standard tyrosine. Amino acid analysis of rhinoceros red blood cell extracts showed that rhinoceros red blood cells did indeed have elevated levels of tyrosine relative to human red blood cells. These levels were in the range of 20 to 50 times that measured in human red blood cells. The peak was then fractionated, concentrated by freeze drying and analysed by mass spectroscopy, which showed that it had the molecular weight expected for the amino acid tyrosine. Red blood cells of wild black rhinoceroses were found to contain 0.78 ± O.llmM (n=8) tyrosine. The finding of such a high concentration of a free amino acid in red blood cells appears to be unprecedented. In an attempt to elucidate the function of tyrosine in rhinoceros red blood cells we drew on the analogy of taurine which is present at very high concentrations in heart epithelial cells and neutrophils. Taurine protects these cells against the respiratory burst oxidants during periods of acute inflammation. Exposure of rhinoceros red blood cells to hydrogen peroxide resulted in the accumulation of dityrosine, a highly fluorescent tyrosine dimer. The formation of dityrosine has previously been shown to occur between protein tyrosyl residues. In our system we describe the crosslinking of free tyrosine in response to hydrogen peroxide in rhinoceros red blood cells. The formation of dityrosine was followed by fluorimetry. Human red blood cells showed no significant production of dityrosine under the same conditions. The accumulation of dityrosine in rhinoceros red blood cells was found to be reciprocally related to GSH concentration. A series of cell-free experiments showed that dityrosine only accumulated in the absence of sufficient GSH and that its production was catalysed by haemoglobin. This study therefore describes the identification of tyrosine present in rhinoceros red blood cells at levels approaching 1 mM. Haemoglobin catalyses the production of dityrosine in response to hydrogen peroxide in a manner that is inversely proportional to the GSH concentration. It is our hypothesis that this tyrosine response to hydrogen peroxide may form a backup antioxidant mechanism for the glutathione peroxidase / reductase system in these cells which are relatively deficient in catalase, a major enzyme for the protection from hydrogen peroxide in other mammals. Analysis of red blood cell extracts of 30 captive black rhinoceroses was found to have significantly lower tyrosine levels (0.37 ± 0.14mM) than the wild rhinoceroses (0.78 ± O.llmM) analysed. These low levels of tyrosine combined with an iron overload syndrome recently described by D. Paglia at UCLA, suggests that black rhinoceroses in captivity may face a higher level of oxidative challenge. The unusual mechanisms in the rhinoceros red cell described here for handling oxidative stress, in which catalase has been replaced by reliance on the glutathione peroxidase system together with a tyrosine buffer, seem to be inadequate under the environmental and dietary circumstances of the captive state. These findings however may give new insight into therapeutic or preventative measures based on dietary modification which will address iron absorption and antioxidants.